Prevalence of COMT Val158Met polymorphism in Eastern UP population - Kumar, P.; Yadav, U.; Rai, V. (Cellular and Molecular Biology, 2017)
Catechol-O-methyltransferase (COMT) is an abundant S-adenosylmethionine (SAM-)-dependent methyltransferase that methylates catechol compounds, including catecholamines and catecholestrogens.COMT  gene located at chromosome 22q11.2 contains a functional polymorphism at codon 158(Val158Met), which has been related to psychiatric diseases and different types of cancer. COMT might affect tHcy levels because as a by-product it converts SAM to S-adenosylhomocysteine (SAH), which is reversibly converted to homocysteine. The aim of the present study was to determine the frequency of COMT Val158Met polymorphism in scheduled caste (SC) population of Jaunpur district. Total 100 healthy unrelated subjects belonging to SC, between the age group of 18 to70 years were randomly selected for the present study. 3 ml blood samples were collected from each subject. The inclusion criteria of subjects for present study are that they should be domicile of Uttar Pradesh, and healthy without any individual/ family history of genetic or metabolic disorders. COMT Val158Met polymorphism analysis was done by PCR-RFLP method. The Val/Val genotype was found in 48 subjects, Val/Met in 40 subjects and Met/Met genotype in 12 subjects. Genotype frequencies of Val/Val, Val/Met and Met/Met were 0.48, 0.40 and 0.12 respectively. The allele frequency of Val allele was found to be 0.68 and Met allele frequency was 0.32.